Natural Resources and Economic Growth: A Meta−Analysis - Mohammad Javad Nourahmadi; Ali Nassiri Aghdam; Mohammad Hossein Aref (جستارهای اقتصادی, 2022)
There have been studies to answer the question of how natural resources affect on economic growth. The answer to this question is very different, some show natural resources have no affect on economic growth, some show a negative impact (resource curse) and others show a positive effect. The purpose of this study is to provide a trendy outcome of the different results of these studies by using a Meta−analysis tool. The hypothesis of this study is that "based on the effect resulting from individual empirical studies, and given the transcription of publishing and heterogeneity, the hypothesis of the natural resource curse is rejected." To this end, we have examined studies by the end of August 2021 according to a specific framework. After studying abstracts, finally 87 single studies, which summarized 1172 regression had a explanatory variable indicating the natural resources, and the text was available, and the results of the regression of these articles carefully selected and addressed the results of these articles. The results of this study show that the natural resources generally have a small negative effect (−0.087) on economic growth. Therefore, the initial hypothesis of this study is rejected, and the size of the total effect shows the resource curse, although its intensity is low according to Cohen's criterion. The present study shows that research has changed the impact of natural resources on economic growth, such as the abundance and dependence of the economy on natural resources, institutional quality, investment, trade freedom, etc in their models.